Computer programming puzzles, mathematics education, and the culture of learning - Gadanidis, George; Hughes, Janette M.; Namukasa, Immaculate; Scucuglia, Ricardo [UNESP] (Taylor & Francis, 2024)
In this chapter, we focus on computer programming puzzles in mathematics education and consider their effect on mathematics teaching and learning in two ways: (1) through the literature in the field, and (2) through an analysis and discussion of a mathematics-oriented computer programming puzzle focusing on the introduction of variables in grades 3-4 (ages 8-10). We conclude that mathematics-oriented computer programming puzzles support and complement a learning culture that values mathematical play, student agency, and conceptual surprise and insight.